2022
DOI: 10.1002/plr2.20229
|View full text |Cite
|
Sign up to set email alerts
|

Registration of the sorghum carbon‐partitioning nested association mapping (CP‐NAM) population

Abstract: The sorghum [Sorghum bicolor (L.) Moench] carbon-partitioning nested association mapping (CP_NAM) (Reg. no. MP-4, NSL 542189 MAP) population was developed at Clemson University, SC, using 11 diverse, male founder accessions, each crossed with a recurrent female parent 'Grassl'. The male parents represent all five major botanical races and the four major agronomic types: cellulosic (5), sweet (3), grain (2) and forage (1). A set of 11 recombinant inbred line (RIL) families CP_NAM01 to CP_NAM011 were maintained,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This section showcases how omic technologies and resources can facilitate biomass studies. Voelker et al reported the genome assemblies of 10 sorghum accessions including sweet and nonsweet sorghum genotypes (Boatwright et al; Kumar et al, 2022). A large number of structural variations (SVs) were identified, which highlighted the SV-related functional difference between sweet and non-sweet sorghum genotypes.…”
Section: Advances In Multi-omic Technologies and Resources Facilitate...mentioning
confidence: 99%
“…This section showcases how omic technologies and resources can facilitate biomass studies. Voelker et al reported the genome assemblies of 10 sorghum accessions including sweet and nonsweet sorghum genotypes (Boatwright et al; Kumar et al, 2022). A large number of structural variations (SVs) were identified, which highlighted the SV-related functional difference between sweet and non-sweet sorghum genotypes.…”
Section: Advances In Multi-omic Technologies and Resources Facilitate...mentioning
confidence: 99%
“…Taken together, these results suggest that unraveling complex traits in sorghum and other crops will require a comprehensive picture of both structural and single nucleotide mutations. In this study, we have expanded on the recently published Carbon-Partitioning Nested Association Mapping (CP-NAM) population that was developed and publicly released as a key genetic resource for the characterization and improvement of sorghum for multiple different end uses ( 2022 ; Boatwright et al., 2021 ; Kumar et al., 2022 ). We generated high-quality de novo genome assemblies for 10 of the CP-NAM parents and used these genomes to identify millions of novel variants, including a number of large structural variants (SVs) occurring in genes or pathways that could be essential for optimizing sorghum as a bioenergy feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results suggest that unraveling complex traits in sorghum and other crops will require a comprehensive picture of both structural and single nucleotide mutations. In this study, we have expanded on the recently published Carbon-Partitioning Nested Association Mapping (CP-NAM) population that was developed and publicly released as a key genetic resource for the characterization and improvement of sorghum for multiple different end uses (Boatwright et al, 2021(Boatwright et al, , 2022Kumar et al, 2022). We generated high-quality de novo genome assemblies for 10 of the CP-NAM parents and used these genomes to identify millions of novel variants, including a number of large structural variants (SVs) occurring in genes or pathways that could be essential for optimizing sorghum as a bioenergy feedstock.…”
Section: Introductionmentioning
confidence: 99%